Flexor Hallucis Longus Tendon Transfer Fixation: A Biomechanical Analysis of the Effects of a Terminal Whipstitch and Bone Tunnel Length. Issue 1 (February 2017) - Lee, Jessica; Williams, Chad; Lowrey, Charles; Gould, Greg; Markert, Ronald; Laughlin, Richard
Introduction . Flexor hallucis longus (FHL) tendon transfer to the calcaneus is commonly used in the surgical treatment of chronic Achilles tendinopathy. This study assesses the integrity of FHL tendon biotenodesis screw fixation with respect to 2 variables: incorporation of a terminal whipstitch and tunnel depth. Materials and methods . A total of 60 fresh-frozen cadaver FHL tendons and 28 calcanei were harvested for analysis in 4 sets of fixation constructs; 14 whipstitched tendons were compared against their nonwhipstitched paired tendon via pull-out strength load testing, and 16 tendon pairs were randomized for fixation in either a full-depth tunnel (bicortical) or a 25-mm partial tunnel (unicortical). All comparisons were carried out in native bone and synthetic models. Results . Whipstitched tendons demonstrated significantly stronger mean clinical load (253.68 vs 177.24 N, P = .008) and maximum load to failure (294.31N vs 194.57 N, P = .001) compared with the nonwhipstitched tendons in synthetic bone. There were no statistical differences in mean clinical load (200.96 vs 228.31 N, P = .63) and maximum load to failure (192.69 vs 217.74 N, P = .73) between full and partial tunnel groups. There were no significant differences found in trials carried out in cadaveric bone. Conclusion . Use of a terminal whipstitch achieves greater fixation strength in FHL tendon biotenodesis transfers. Complete and partial tunnel constructs are equivocal in their pull-out strength. Data produced in a homogeneous bone substitute model demonstrate the biomechanical superiority of the whipstitch as well as the noninferiority of the partial tunnel technique. Levels of Evidence: Level IIb